MEASURE OF INEQUALITY AND IMPROVED CLASSIFICATION ACCURACY USING PMTCT HIV DATA - S.SANTHOSH KUMAR (International Journal of Pharma and Bio Sciences, 2016)
HIV (Human Immunodeficiency Virus) is a lent virus that causes Acquired Immune Deficiency Syndrome (AIDS). It is an epidemic which causes a progressive failure of immune system in the human body. All countries are maintaining HIV . data repositories to monitor, share the needful information. For detailed investigation and diagnosis processes, the HIV data need to be categorized based on its generic variability, sub types and mode of transmission. The transmission of HIV mother to her child is one of the major causes of HIV transmission. It happens during pregnancy, labour, delivery and breastfeeding is called mother-to-child transmission One of important goal is to prevent mother to child HIV transmission (PMTCT). It is a global commitment accelerated by UNICEF, UNO, WHO and other organizations. These initiatives started very recent and hence the least amount of data is available about PMTCT. Mostly collected (PMTCT) data are with fewer interventions. When it is used for various clinical implications, it gives poor results with least accuracy. This paper focuses to handle the inconsistent data related to accuracy rate.